Synthesis of Au@Ni bimetallic core shell nanoparticle and nanochains in soyabean oil and their catalytic hydrogenation reactions. Issue 2 (5th February 2016) - Bharathan, Vysakh A.; Yadukiran, V.; Lazar, Anish; Singh, Anand. P.; Vinod, Chathakudath P.
Abstract: Synthesis of Au@Ni bimetallic core shell nanostructures using commercially available soya bean oil as the solvent through a sequential reduction strategy is reported. The energy efficiency and economic viability comes from the much milder temperatures and replacement of expensive and environmentally hazardous solvents like long chain organic amines and acids previously reported for synthesis. Thus, core shell nanoparticles having size regime of 10‐15 nm with an excellent control over the nickel shell thickness (2 nm) over the gold core (8‐10 nm) and Au@Ni nanochains is achieved. The synthesized materials are demonstrated to synergistically catalyze hydrogenation of nitro and C‐C multiple bonds with much better efficiency as compared to individual nanoparticle counterparts. Abstract : Going green with soyabean : Use of soyabean oil for the synthesis of Au@Ni core shell nanoparticles and nanochains is demonstrated. Because of the surface modification due to gold core, the nanostructures are shown to synergistically catalyse hydrogenation reactions.